Telmisartan reverses hepatic steatosis via PCK1 upregulation: A novel PPAR-independent mechanism in experimental models of MASLD - Roger Bentanachs; Patricia Ramírez-Carrasco; Bianca Braster; Anastasia Emmanouilidou; Endrina Mujica; Maite Rodrigo-Calvo; Cristina Rodríguez; Núria Roglans; Marcel den Hoed; Juan C. Laguna; Marta Alegret (Pharmacological Research)
Drug combination and repurposing are potential therapeutic strategies for the treatment of metabolic dysfunction-associated steatotic liver disease (MASLD). Here, we have demonstrated that, in rats, both pemafibrate and telmisartan reverse hepatic steatosis induced by a high-fat, high-fructose diet. Pemafibrate attenuated liver steatosis via a PPARα-mediated increase in fatty acid catabolism, while the antisteatotic response to telmisartan did not rely on PPAR modulation. Our results in rats and in a zebrafish larva model of liver lipid accumulation suggest that part of telmisartan’s antisteatotic effects are driven through the blockade of the angiotensin II type 1 receptor, along with a reduction in the expression of several lipogenic genes, which also contributes to some extent. Telmisartan’s response is mediated by the upregulation of hepatic phosphoenolpyruvate carboxykinase 1 (PCK1) expression. Liver metabolomic analysis revealed that by increasing PCK1, telmisartan diverted the metabolic flux of fructose from lipid towards glucose synthesis, which was subsequently fueled to the polyol pathway, thereby preserving glucose homeostasis. Moreover, telmisartan increased the hepatic levels of spermine and spermidine, which may counteract the putative detrimental effects caused by the accumulation of metabolites of the polyol route. Targeting different intrahepatic pathways, both PPAR-dependent and independent, the combination of pemafibrate and telmisartan, each at half the individual dose, was equally effective as the full dose of either drug alone to reduce liver lipid accumulation in the rat model. Our findings support the repurposing potential of these drugs, with the additional advantage of addressing both hepatic and cardiometabolic MASLD-associated complications.